Fumarase Overexpression Abolishes Hypertension Attributable to eNOS Haploinsufficiency in Dahl Salt-Sensitive Rats - Xue, Hong (Hypertension, 2019)
Human blood pressure salt sensitivity is associated with changes in urinary metabolites related to fumarase (Fh) and nitric oxide (NO) metabolism, and fumarase promotes NO production through an arginine regeneration pathway. We examined the role of the fumarase-NO pathway in the development of hypertension using genetically engineered rat models. Dahl salt-sensitive (SS) rats with heterozygous mutation of endothelial NO synthase (eNOS or Nos3) (SS-Nos3(+/−)) were bred with SS rats with a hemizygous Fh transgene. SS-Nos3(+/−) rats without the Fh transgene (SS-Nos3(+/−)/Fh(0/0)) developed substantial hypertension with a mean arterial pressure (MAP) of 134.2 ± 3.7 mmHg on a 0.4% NaCl diet, and 178.0 ± 3.5 mmHg after 14 days on a 4% NaCl diet. MAP decreased remarkably to 123.1 ± 1.4 mmHg on 0.4% NaCl, and 143.3 ± 1.5 mmHg on 4% NaCl in SS-Nos3(+/−) rats with a Fh transgene (SS-Nos3(+/−)/Fh(0/1)), and proteinuria, renal fibrosis, and tubular casts were attenuated in SS-Nos3(+/−)/Fh(0/1) rats compared to SS-Nos3(+/−)/Fh(0/0) rats. eNOS protein abundance decreased in rats with the Nos3 heterozygous mutation, which was not influenced by Fh overexpression in rats on the 0.4% NaCl diet. However, the decrease in NO metabolite in the renal outer medulla of SS-Nos3(+/−)/Fh(0/0) rats on the 0.4% NaCl diet was reversed in SS-Nos3(+/−)/Fh(0/1) rats, and levels of L-arginine, but not the other 12 amino acids analyzed, were significantly higher in SS-Nos3(+/−)/Fh(0/1) rats than in SS-Nos3(+/+)/Fh(0/0) rats. In conclusion, fumarase has potent effects in restoring NO production and blunting the development of hypertension attributable to eNOS haploinsufficiency.